2021
DOI: 10.1101/2021.11.02.465022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Powerful synergistic effects of a STING agonist and an IL-2 superkine in cancer immunotherapy against MHC I-deficient and MHC I+ tumors

Abstract: Cyclic dinucleotides (CDNs) and TLR ligands mobilize antitumor responses by NK cells and T cells, potentially serving as complementary therapies to immune checkpoint therapy. In the clinic thus far, however, CDN therapy has yielded mixed results, perhaps because it initiates responses potently, but does not provide signals to sustain activation and proliferation of activated cytotoxic lymphocytes. To improve efficacy, we combined CDNs with a half-life extended IL-2 superkine, H9-MSA. CDN/H9-MSA therapy induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…STING silencing is a mechanism used by tumors to quiet immune responses (399, 400), and activating STING can enhance NK-cell mediated immunotherapy (401,402) and NK cell trafficking via CXCR3 (401,402). IL-2 and STING-agonists together support T and NK cell activation against treatment-refractory mouse tumor models (401,403). Potentially identifying a mechanism that contributes to these responses, a recent single-cell approach identified that STING mediates its anti-tumor immune stimulating impact, in part, through CXCR3 upregulation and the subsequential recruitment and activation of NK cells (402).…”
Section: • Carcinoembryonic Antigen-related Cell Adhesionmentioning
confidence: 99%
“…STING silencing is a mechanism used by tumors to quiet immune responses (399, 400), and activating STING can enhance NK-cell mediated immunotherapy (401,402) and NK cell trafficking via CXCR3 (401,402). IL-2 and STING-agonists together support T and NK cell activation against treatment-refractory mouse tumor models (401,403). Potentially identifying a mechanism that contributes to these responses, a recent single-cell approach identified that STING mediates its anti-tumor immune stimulating impact, in part, through CXCR3 upregulation and the subsequential recruitment and activation of NK cells (402).…”
Section: • Carcinoembryonic Antigen-related Cell Adhesionmentioning
confidence: 99%